Urgensi Perlindungan Anak Korban Eksploitasi Seksual: Telaah Hukum Nasional dan Thailand - Stevaniya Tarigan; Atikah Rahmi (Jurnal Hukum Lex Generalis, 2025)
Child exploitation is a significant global issue, particularly in Southeast Asia, including Indonesia and Thailand. This study aims to examine the legal regulations in Indonesia and Thailand regarding child exploitation and to understand the urgency of legal protection for child victims of sexual exploitation in both countries. A normative juridical research method is employed to analyze how these countries handle child exploitation cases, focusing on legal standards and their implementation. The study compares the laws in both nations and evaluates their application in child exploitation cases. The findings indicate that Indonesia's legal framework for addressing child exploitation refers to Article 76I in conjunction with Article 88 of the Child Protection Law (UUPA) and Article 12 in conjunction with Article 13 of the Law on Sexual Violence Crimes (UUTPKS). In Thailand, child exploitation is regulated under the Thailand Penal Code and the Child Protection Act of 2003. When applying Indonesian law to offenders of child exploitation crimes occurring in Thailand, it is essential to consider the United Nations Convention on the Rights of the Child (CRC) of September 2, 1990. Legal protection for child victims of sexual exploitation in Indonesia varies according to the provisions of the Child Protection Law. Meanwhile, Thailand implements protection measures through national campaigns, strategic policies, and international cooperation. Keywords: Law, Indonesia, Thailand, Child Exploitation